Biosensor and bioelectrocatalysis studies of enzymes immobilized on graphite electrode materials - Schneider, B. H. (Cranfield University, 1987)
The immobilization of glucose oxidase and lipoamide dehydrogenase on graphite electrodes was studied for their application in mediated bioelectrochemical systems. These are techniques where the electrons involved in an enzymatic redox reaction are either supplied by, or given to an electrode from the enzyme. In the biosensor mode, where a current is measured due to product oxidation, the immobilized enzyme may be used to monitor its substrate, for example a biosensor for glucose based on the enzyme glucose oxidase. In the bioelectrosynthesis mode, when a cathodic potential is applied to the electrode, electrons may be transferred to the enzyme via a mediator thereby driving a thermodynamically difficult reaction, such as the reduction of the coenzyme NAD+ . A glucose sensor based on glucose oxidase immobilized onto graphite foil electrodes which had been doped with the mediator dimethylferrocene was found to produce both a linear and rapid response to changes in glucose concentration in solution. The kinetics of this particular system were studied in depth in order to explain its behaviour. Results showed that the porous nature of the electrode material resulted in immobilization of the enzyme throughout a number of layers• Consequently, diffusion of glucose into the electrode became the rate limiting process at low glucose concentrations, which resulted in linear calibration curves. This was characterized by a substrate modulus, which was found to be sufficiently large to predict diffusional limitations. From this the effective rate of glucose diffusion within the electrode was estimated, and found to be up to 5 times smaller than that in free solution. The rapid response of the sensor, on the other hand, was due to the absence of any mass transfer limitations external to the electrode surface. When lipoamide dehydrogenase was employed in the same system it was found that complications arose due to coupling of NADH oxidation with the adsorbed mediator. By employing a less anodic potential of +150 mV vs. Ag/AgCl at NADH concentrations below 1 mM the detection of enzymatic oxidation of the coenzyme was achieved. Enzymatic reduction of NAD+ was achieved using lipoamide dehydrogenase immobilized onto graphite felt electrodes. This reaction was mediated by methyl viologen, with the enzyme-modified electrode used to reduce the mediator at a potential of -0.7 V ( vs. SCE ). In this fashion the reduced form of methyl viologen was recycled, thereby driving the reduction of NAD . By coupling this system to lactate dehydrogenase it was possible to effect the reduction of pyruvate.